Empire of cotton: A new history of global capitalism - Beckert, Sven (Great Britain Penguin Books, 2015)
This book is the winner of the 2015 Bancroft Prize and the 2015 Philip Taft Prize. It is the finalist for the 2015 Pulizter Prize for History and shortlisted for the 2015 Cundill Prize in Historical Literature. For about 900 years, from 1000 to 1900, cotton was the world's most important manufacturing industry. It remains a vast business - if all the cotton bales produced in 2013 had been stacked on top of each other they would have made a somewhat unstable tower 40,000 miles high.